2019
DOI: 10.4322/rbcv.2019.017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mineral concentrations on hooves of horses, mules and donkeys

Abstract: Differences in mineral concentrations on hooves of horses, mules and donkeys* Diferenças nas concentrações de minerais nos cascos de equinos, muares e asininos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…This value was somewhat similar to that obtained by de Souza et al, 3.51 ± 1.6 ppm ( 30 ), but it was found below (4.3–4.53 ppm) that described by Faria et al ( 32 ). In another study, by de Souza et al, Cu values of 5.61 ± 1.38 ppm were recorded ( 11 ). Copper has a very specific role in the growth of the hoof, as it is essential to build the keratin bridges present in the hoof.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This value was somewhat similar to that obtained by de Souza et al, 3.51 ± 1.6 ppm ( 30 ), but it was found below (4.3–4.53 ppm) that described by Faria et al ( 32 ). In another study, by de Souza et al, Cu values of 5.61 ± 1.38 ppm were recorded ( 11 ). Copper has a very specific role in the growth of the hoof, as it is essential to build the keratin bridges present in the hoof.…”
Section: Discussionmentioning
confidence: 89%
“…The K levels determined (3,416 ± 3,270 μg/g) were higher than those mentioned by Sargentini et al (1,690 ± 112 ppm) ( 24 ) and de Souza et al (460 ± 425 ppm) ( 31 ). With regard to Mg, values of 181 ± 98 μg/g were obtained, while in mules and donkeys, de Souza et al ( 11 ) indicated values of 840 ± 922 ppm and 1,178 ± 855 ppm, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Залишок копитної стінки зберігає 9 рогових трубочок на мм². Тобто у віслюка спостерігається чітка тризонна ступінчаста схема щільності рогових трубочок у середньому шарі копитної стінки [14,30,39].…”
Section: рис 8 сагітальний розріз пальця віслюка (зліва) та коня (справа)unclassified